An Analysis of Mood and Modality - Yuni Siregar; Arsen Nahum Pasaribu; Erika Sinambela (Pioneer: Journal of Language and Literature, 2021)
Since the outbreak of Coronavirus in 2020, teaching and studying activities commonly conducted in the classrooms were shifted to online, which caused students to adapt and accept without compromising. This study analyzed the dialogue texts expressing students' hopes and views about the future of learning amidst the Covid-19 pandemic written by the Senior High School students of Nanyang Zhi Hui school in Medan, Sumatera Utara. The objectives are to analyze the mood, modality, and modality orientation types; and figure out the dominantly-applied mood, modality, and orientation types in the dialogue texts. This descriptive qualitative research applied the Mood and Modality theory by Halliday and other linguists. The study revealed that 1) three mood types: declarative, interrogative, and imperative, four types of modality: probability, usuality, obligation, and inclination range from low, median, and high degrees; four orientations: subjective-explicit, subjective-implicit, objective-explicit, and objective-implicit occurred in the texts; and 2) the clauses are represented through the extensive use of declarative mood (80,74%), median probability (47%), and implicitly objective modality orientation (45,15%). The study concludes that the students tend to give their insights using statements with median probability and orientation of objective-implicit in the dialogue, which shows a lack of confidence in the utterances.